Nearly Completely Positive Graphs. - Xu, Changqing (Applicable algebra in engineering, communication and computing.)
A non-cp graph G is called nearly vertex (edge) cp if any subgraph of G obtained by deleted a vertex (an edge) of G is completely positive. This paper presents necessary and sufficient conditions for any doubly nonnegative matrix realization A of a nearly cp graph to be completely positive.